2008
DOI: 10.1007/s11099-008-0018-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of effects of salt and alkali stresses on the growth and photosynthesis of wheat

Abstract: The seedlings of wheat were treated by salt-stress (SS, molar ratio of NaCl : Na 2 SO 4 = 1 : 1) and alkali-stress (AS, molar ratio of NaHCO 3 : Na 2 CO 3 = 1 : 1). Relative growth rate (RGR), leaf area, and water content decreased with increasing salinity, and the extents of the reduction under AS were greater than those under SS. The contents of photosynthetic pigments did not decrease under SS, but increased at low salinity. On the contrary, the contents of photosynthetic pigments decreased sharply under AS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
119
2
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(136 citation statements)
references
References 26 publications
14
119
2
1
Order By: Relevance
“…T2, T3, and T4 were lower than the control plants in terms of plant dry weight. Previous studies have also found that high pH (Yang et al, 2008) and bicarbonate ions (Mengel, 1994;Pestana et al, 2005) decrease plant growth and development. In this study, high pH and low iron had a significant effect on reducing dry weight.…”
Section: Discussionmentioning
confidence: 88%
“…T2, T3, and T4 were lower than the control plants in terms of plant dry weight. Previous studies have also found that high pH (Yang et al, 2008) and bicarbonate ions (Mengel, 1994;Pestana et al, 2005) decrease plant growth and development. In this study, high pH and low iron had a significant effect on reducing dry weight.…”
Section: Discussionmentioning
confidence: 88%
“…Comparing alkali stress with salt stress, the high pH environment that surrounds the plant root can cause the precipitation of metal ions and phosphorus, greatly affecting the absorption of inorganic anions and disrupting the ionic balance and pH homeostasis in plant tissues (Shi and Zhao 1997;Yang et al 2007Yang et al , 2008c. It is understood that currently, only a few plant species of alkali-resistant halophytes can survive in saline and alkaline land (Zheng and Li 1999;Yang et al 2008a).…”
Section: Discussionmentioning
confidence: 99%
“…Photosynthetic capacity has been observed to be much lower under both salt and alkali stresses than in control plants in the glycophytes wheat and barley, and the inhibition was more severe under alkali stress than salt stress (Yang et al 2008c). However, the situation is different in the halophyte Chloris virgata, whose photosynthetic properties were not influenced by salt and alkali treatment below 160 mM (Yang et al 2008a).…”
Section: Photosynthesismentioning
confidence: 99%
“…The results revealed that alkaline stress might damage root functions, including, the absorption of water and ions. These may be the main reasons why the oat RGR was lower for alkaline than saline stress (Yang et al, 2008).…”
Section: Growthmentioning
confidence: 98%